APAKAH TERDAPAT PENGARUH MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA MELALUI SELF REGULATION? - Lutfa, Innani Nadya; Rukmigarsari, Ettie; Wulandari, Tri Candra (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to determine the influence of learning interest on students' mathematics learning outcomes through self-regulation. The type of research used in this study is ex-post facto. The population in this study is all students of class X of SMAN 1 Tumpang. The sampling technique used is cluster random sampling. The sample in this study is 71 students. There are 3 variables in this study, namely learning interest (exogenous variable), self-regulation, (intervening variable) and mathematics learning outcomes (endogenous variable). The instruments used for data collection are questionnaires and tests. The questionnaire instrument consists of a learning interest questionnaire and a self-regulation questionnaire. The test instrument is in the form of essay questions on students' mathematics learning results on row and row material. The scores of the learning interest questionnaire and self-regulation, which are ordinal data, were transformed into interval data using the Method of Successive Interval (MSI). Then a normality test was carried out as a condition for a parametric statistical test. The data analysis technique used is path analysis. The results of this study show that learning interest has a positive and significant effect on students' mathematics learning outcomes both directly and indirectly through self-regulation.